111 Extravalvular cardiac damage and renal function following TAVI for severe aortic stenosis. (8th December 2021) - Fezzi, Simone; Pesarini, Gabriele; Mammone, Concetta; Flaim, Massimo; Castaldi, Gianluca; Tavella, Domenico; Scarsini, Roberto; Ribichini, Flavio; Pighi, Michele
Abstract: Aims: Acute kidney injury (AKI) represents a common complication following TAVI, that correlates strictly with in-hospital, short, and long-term mortality. Extra-valvular cardiac damage (EVCD) showed to affect long-term outcomes in patients with severe aortic stenosis (AS). We sought to determine the differences in the incidence of AKI and acute kidney recovery (AKR) among patients undergoing TAVI and their impact on clinical outcomes according to EVCD. Methods and results: 706 symptomatic severe AS patients were selected and retrospectively analysed. Based on echocardiography findings, patients were classified based on the degree of EVCD. AKI was defined as a relative increase at 24–72H in sCr concentration of at least 0.3 mg/dl, and was classified according to AKIN stages. AKR was defined either as an increase of GFR of 25% or a decrease in sCr of at least 0.3 mg/dl, both measured at 24–72H after the procedure. After dichotomized analysis, patients in EVCD stage 3–4 reported a significantly higher rate of AKI (27.4% vs. 11.3%; P  < 0.001), significant AKI (5.3% vs. 1.5%; P  < 0.010) and the need for continuous renal replacement therapy (CRRT) after TAVI (2.7% vs. 0.7%; P  = 0.052), whereas a lower incidence of AKR was reported (11.6% vs. 6.2%; P  = 0.087). At the multivariate model higher EVCD stage, lower GFR and the amount of contrast used were found to be independent predictors of AKI, while early stages of cardiac damage (HR: 0.420; 95% CI: 0.224–0.785; P  = 0.007) and lower GFR were found to be independent predictors of AKR. In the overall population, at a median 24-months follow-up, after multivariate analysis AKI was associated with a higher incidence of all-cause mortality [HR: 2.636; 95% CI: (1.360–5.108); P  = 0.004] and MACEs [HR: 2.122; 95% CI: (1.170–3.849); P  = 0.013]. Notably, at the multivariate analysis, AKI significantly impacted on survival in patients in stages 3–4 [HR: 2.461; 95% CI: (1.017–6.067); P  = 0.046], but not in patients in stages 0–2 [HR: 1.301; 95% CI: (0.380–4.457); P  = 0.675], with an interaction that achieved statistical significance ( p for interaction 0.006). AKR did not reduce adverse clinical outcomes [HR: 0.742; 95% CI: (0.339–1.623); P  = 0.455 for all-cause mortality; HR: 0.701; 95% CI: (0.351–1.397); P  = 0.312 for MACEs] but was associated with an improvement of renal function at 12 months. Conclusions: AKI demonstrated to negatively impact on 24-month all-cause mortality only when occurring in advanced stages of EVCD, but not in early stages. Conversely, early EVCD was associated with a higher incidence of AKR, which not significantly improved clinical outcomes but was associated with an improvement of renal function at 12-months. The application of this staging system may provide an additional tool for the decision-making process in patients with severe AS.